TikTok war humor: social and psychological functions of humor videos by micro-influencers and ordinary users during conflict - Steinfeld, Nili; Rosenberg, Hananel; Mahat-Shamir, Michal (Frontiers in Psychology, 2025)
While much research highlights the negative psychological impacts of social media use, the current study examines how, in the aftermath of collective trauma, social media platforms can serve as spaces for resilience-building through the creative use of humor. On October 7, 2023, Hamas launched a large-scale surprise attack on Israel from the Gaza Strip, resulting in over 1,200 Israeli casualties, 253 hostages, and extensive damage. Recognized as the deadliest terrorist attack in Israel’s history, it led to a war, causing significant distress and trauma among all the peoples of the region. Surprisingly, just days after the attack, humorous videos emerged on TikTok, uploaded by Israeli influencers, citizens, and reservists. This study examines the interaction between humor, TikTok performance, and public trauma during war. A quantitative content analysis of 257 TikTok videos from the initial post-October 7th period identified the styles, characteristics, and psychological functions of humor, and the unique nature of TikTok humor. Additionally, a thematic analysis of in-depth interviews with seven Israeli TikTok influencers explored their motivations for creating and sharing humorous content during this period and the influence of audience interactions on their actions. Findings show that humorous content followed platform rules, with trends, TikTok formats, and parodies being dominant. Creators aimed to boost morale while avoiding controversial political topics. Civilians and soldiers used humor differently: civilians focused on coping and stress at home, while soldiers focused on frontline and army routine. Interviews revealed TikTok as a therapeutic space, with humor serving as a defense mechanism. The creative process was calculated, filled with uncertainties and heightened sensitivity, as creators and users practiced resilience-building during their darkest hours.